Hubungan Dukungan Keluarga dengan Tingkat Depresi pada Pasien Gagal Ginjal Kronik yang Menjalani Terapi Hemodialisa - Riyadi; Siagian, Ira Ocktavia; Saragih, Berlyna D (STIKES Ngesti Waluyo, 2023)
Hemodialysis is a process of removing metabolic wastes, and it is used to optimize kidney function that has experienced permanent failure. Hemodialysis can lead to changes in the physical and psychological aspects of the patient's life and it can be a trigger for excessive stressors that can lead to depression. Therefore, family support is needed in the management of providing support to patients. The purpose of this study was to determine the relationship between family support and the level of depression in patients undergoing hemodialysis therapy. This type of research is a correlational research with a cross sectional approach. The number of samples is 60 respondents with total sampling technique. Data collection was obtained through family support questionnaire and Beck Depression Inventory-II (BDI) questionnaire. The test data analysis used was Spearman Rank test. The results of the study showed a significance value of 0.000 (p<0.05), which means that there is a relationship between family support and the level of depression in patients undergoing hemodialysis therapy. There is a significant relationship between family support and the level of depression in patients undergoing hemodialysis therapy at the hemodialysis unit. It is hoped that this research can be an input for the nursing profession to provide holistic bio-psycho-social nursing care for patients with chronic kidney failure to reduce depression and improve family-centered care.